2019
DOI: 10.2174/1871520619666181207094243
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inhibitors of DNA Repair Enzyme TDP1 Combining Monoterpenoid and Adamantane Fragments

Abstract: Background and Objective: The DNA repair enzyme tyrosyl-DNA-phosphodiesterase 1 (TDP1) is a current inhibition target to improve the efficacy of cancer chemotherapy. Previous studies showed that compounds combining adamantane and monoterpenoid fragments are active against TDP1 enzyme. This investigation is focused on the synthesis of monoterpenoid derived esters of 1-adamantane carboxylic acid as TDP1 inhibitors. Methods: New esters were synthesized by the interaction between 1-adamantane carboxylic acid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…The compounds synthesized can be divided in to two groups: (1) amides and thioamides of 1-and 2-adamantane carboxylic acids (44a,b; 45a,b; 46a; 47a); (2) derivatives of citronellic acid (50a,b; 51). Comparing inhibitory activity of the first group (Table 1) and compounds synthesized previously [49] it can be concluded that amides 44-47 are less active than their ester counterparts are. For example, in the cases of derivatives 29 (ester), 44 (amide), 48 (thioamide), which are structural analogues, the following IC 50 values were obtained: 0.92, >75 and 3.3 µM, respectively.…”
Section: Inhibition Studiesmentioning
confidence: 94%
See 3 more Smart Citations
“…The compounds synthesized can be divided in to two groups: (1) amides and thioamides of 1-and 2-adamantane carboxylic acids (44a,b; 45a,b; 46a; 47a); (2) derivatives of citronellic acid (50a,b; 51). Comparing inhibitory activity of the first group (Table 1) and compounds synthesized previously [49] it can be concluded that amides 44-47 are less active than their ester counterparts are. For example, in the cases of derivatives 29 (ester), 44 (amide), 48 (thioamide), which are structural analogues, the following IC 50 values were obtained: 0.92, >75 and 3.3 µM, respectively.…”
Section: Inhibition Studiesmentioning
confidence: 94%
“…Intrinsic protein fluorescence assay were conducted according to the protocol as described in references [35,45,49]. The concentrations of recombinant Tdp1 and ligand were 10 µM and 1 mM, respectively.…”
Section: Binding Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…been developed based on adamantane [4][5][6][7][8]. The mechanism of action of adamantane derivatives that belong to the class of actoprotectors (bromantane, chlodantan) is related to the increased synthesis of dopamine and inhibition of the process of lipid peroxidation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%